Pengaruh Suplementasi L-Threonine dalam Pakan terhadap Berat Potong dan Berat Non Karkas Ayam Broiler - Irna Oktoviana Selan; Charles Venirius Lisnahan; Oktovianus Rafael Nahak (JAS, 2022)
The research aim was to know the effect of l-threonine supplementation on slaughter weight and non-carcass weight of broilers. This research was conducted in Kampung Bima, Kelurahan Kefa Selatan, North Central Timor Regency, and the Laboratory of the Faculty of Agriculture, University of Timor, Kefamenanu for 7 weeks, from December 2019 to January 2020. The research used 80 fourteen-day broilers. The research was designed with a Completely Randomized Design, consisting of 4 treatments and 4 replications. The dietary treatments were T0 (control feed), T1 (supplementation of 0.5% l-threonine), T2 (supplementation of 0.1% l-threonine), and T3 (supplementation of 1.5% l-threonine). The variables measured were slaughter weight and non-carcass weight. Data obtained was analyzed by analysis of variance and Duncan’s test. The results showed that the average slaughter weight for T0, T1, T2, and T3 were 1737.50±15.50, 1795.75±13.23, 1795.75±13.23, and 1902.00±63.97g/bird, respectively. The percentage of slaughter weight, blood weight, the percentage of blood weight,feather-weight, the percentage of feather-weight, non-carcass weight, and the percentage of non-carcass weight were 96.84±0.12; 96.64±0.11; 96.33±0.09; 96.52±0.15 %/bird; 56.75±2.06, 62.50±1.91, 76.25±2.87, and 68.50±2.38g/bird; 3.16±0.12, 3.37±0.11, 3.67±0.09, and 3.48±0.15 %/bird; were 71.75±10.31, 65.25±7.18, 72.25±9.78, and 72.25±8.22 g/bird; were 3.99±0.57, 3.51±0.38, 3.47±0.32, and 3.67±0.48 %/bird; 506.56±5.30, 495.98±21.36, 530.78±20.30, and 537.80±26.07 g/bird; and 28.24±0.54, 26.69±1.08, 25.53±0.38, and 27.29±0.88 %/bird, respectively. It was concluded that supplementation with 1.0% of l-threonine improved the growth performance of broilers.